The deer from the early Middle Pleistocene site of Isernia la Pineta (Molise, Italy): revised identifications and new remains from the last 15 years of excavation. (28th January 2015) - Breda, M.; Peretto, C.; Thun Hohenstein, U.; Donovan, Stephen K.; Stringer, Christopher B.
<x xml:space="preserve">Abstract</x> The deer remains from the renowned Palaeolithic site of Isernia la Pineta (southern Italy) are revised. Both material already published, and new specimens from the last 15 years of excavation, is taken into account and some identifications are revised. The published assemblage consists of Megaceroides solilhacus, Cervus sp. cf. C. elaphus acoronatus, Dama sp. cf. D. clactoniana and Capreolus sp. The literature dealing with these species is discussed and the problems still unresolved are outlined. The giant deer, now assigned by most authors to the genus Praemegaceros as P. solilhacus, is the largest and most common deer species at the site, represented by numerous antler fragments plus a few isolated teeth and fragmentary postcranial elements. The retrieval of new, well‐preserved specimens, namely one nearly complete antler, plus a distal portion of palmation, two neural skulls and one premaxillary bone, allows a better characterization of this otherwise still poorly understood species. The sub‐specific attribution of the red deer, in the lack of more complete antler specimens, is still dubious. The fallow deer remains probably belong to Dama roberti, a recently described species from the early Middle Pleistocene of Western Europe. The morphology of the lower portion of the only preserved antler fits better with this species rather than with D. clactoniana, to which it was previously tentatively assigned. At last, the specific identity of the few roe deer remains from Isernia is discussed, but the problem remains unanswered because of lack of agreement, in the literature, about the taxonomy of the Pleistocene species. Copyright © 2015 John Wiley & Sons, Ltd.